IMPACT ASSESSMENT ON THE HYDRODYNAMICS OF THE SAN QUINTIN BAY LAGOON, BAJA CALIFORNIA -MEXICO: DEEPENING A NORTHEAST REGION - Santillan, Maria Fernanda Morales (2020)
Commonly, coastal water bodies are subject to anthropic action due to the various human activities that take place near the coast. Any change in the coastline or coastal sea bed directly impacts the behavior of the local water movement. It is extremely